Gill Structure of Pangasius polyuranodon From Up and Down Stream Of Siak River - Riska Puspita Sari; Ridwan Manda Putra; Windarti ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
Siak River is the most polluted river in Riau, however, many types of fish, including Pangasius polyuranodon living in that river. As the water is polluted the health of the fish in general, including its gill structure might be harmed. A study aims to understand the histological structure of the gill of fish from upstream and downstream of the Siak River has been conducted in May 2015. Abnormality in the gill was noted and the abnormality level was identified using a Histopathological Alteration Index (HAI). Results shown that the types of abnormality present were hyperplasia, hypertrophy, atrophy and deformated lamella. The HAI level was 2.67-2.75, indicates that the gill of the P. polyuranodon from the Siak River was normal.Keyword: Siak River, Histopathological Alteration Index , gill structure, Pangasius polyuranodon